Pengaruh Pemberian Kombinasi Ekstrak Tanaman Kemangi (Ocimum basilicum) dan Daun Salam (Syzygium polyanthum) sebagai Pestisida Alami untuk Mengendalikan Serangga Hama pada Tanaman Kangkung Darat (Ipomoea reptans Poir) - Noer Ashikin; Sonja Verra Tinneke Lumowa; Makrina Tindangen; Dora Dayu Rahma Turista (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The decline in land spinach (Ipomoea reptans Poir.) production is partly due to pest attacks, such as armyworms, aphids, and whiteflies. This study aims to determine the effect of a combination of basil (Ocimum basilicum) and bay leaf (Syzygium polyanthum) leaf extract as a botanical pesticide on pest attack intensity and to determine the most effective concentration. This study used a Randomized Block Design (RBD) with five treatments (0%, 30%, 40%, 50%, and 60%) and five replications. The analysis results showed that the combination of the two leaf extracts significantly reduced pest attack intensity. The 60% concentration resulted in the lowest attack intensity, at 18% (mild category), making it the most effective treatment. Thus, the combination of basil and bay leaf extracts has the potential to be an environmentally friendly botanical pesticide for pest control in land spinach.